(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The constant growth of the population and the increasing demand for resources, coupled with shortages of food, raw materials, and habitat, highlight the urgent need to study both Uzbek and foreign experience to find solutions to these problems. Environmental pollution, the ongoing trend of increasing carbon dioxide and other greenhouse gas emissions leading to climate change, exacerbate the previously noted problems. The paper considers and analyzes the main features and aspects of the circular economy concept, which is replacing the conventional linear economic development model.